Pedagogic theories in Rural Education: perceptions and confirmations from the analysis of political-pedagogical projects in the context of Ação Escola da Terra at UFBA - Manoel Gonçalves dos Santos; Luiz Bezerra Neto (Universidade Federal do Norte do Tocantins, 2022)
In the article, we compare pedagogical theories in movement in rural education, based on propositions of political-pedagogical projects in five municipalities in Bahia whose teachers from schools located in rural areas participated in the formation of the Ação Escola da Terra promoted by UFBA. Such comparison aimed to verify to what extent the pedagogical theories that underlie these documents approach or distance themselves from the assumptions of historical-critical pedagogy, understanding that the level of approximation implies an element that could favor, or not, an effective implementation of this pedagogical aspect in the researched educational contexts. The result of the documental analysis revealed that the pedagogy of popular education, the pedagogies of practice and the pedagogies of learn to learn prevail in the field of education in these contexts, characterizing a theoretical eclecticism, which constitutes an obstacle, although not decisive, for the implementation of historical-critical pedagogy in rural education in these municipalities.